Development Of Economic Mathematics Learning System Through Master Model For Students Of Economic Education Study Program - Mayasari, Mayasari; Hidayati, Umi; Muslim, Fachruddiansyah; Aisyah, Nur; Hutabarat, Zuhri Saputra; Mareta, Yoan (Politeknik Ganesha Medan, 2024)
The purpose of this study is 1) to identify the need for the development of an Economic Mathematics Learning System through the MASTER Model for students of the Economic Education Study Program in participating in the learning process, 2) to develop a tool for making Economic Mathematics Learning System Development through the MASTER Model for students of the Economic Education Study Program in following the process learning, and 3) measuring or knowing the validity of the Economic Mathematics Learning System through the MASTER Model for students of the Economic Education Study Program in participating in the lesson. The study results found that the validation of material experts and learning system experts (learning models), it can be seen that results of the validation of material experts are 4,44 or good and the results of validation by media experts are 4.33 or good. The results of interviews with lecturers and students as a whole showed good responses to the use of the MASTER learning model in the learning process.